2020
DOI: 10.1111/jfpe.13510
|View full text |Cite
|
Sign up to set email alerts
|

A moisture content prediction model for deep bed peanut drying using support vector regression

Abstract: In order to make the moisture content monitoring more convenient and rapid during peanut drying process, the drying characteristics of peanut were investigated and a real‐time SVR moisture content monitoring model was established in this paper. The results showed that hot air temperature, initial moisture content, airflow rate and the layer height were the key factors on peanut drying, and the peanut variety showed little effect on drying. The SVR model exhibited a good performance with R2: 0.91, RMSE: 4.38, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The rice variety named NJ5055 is used in this study and obtained by manual hulling. The moisture content of brown rice can be obtained using several approaches (Lu et al, 2018; Qu et al, 2020), for example, the thermogravimetric method, as shown in Figure 1a. The rice specimens are stored at constant temperature and humidity chamber with the relative humidity of 65% and the air temperature of 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The rice variety named NJ5055 is used in this study and obtained by manual hulling. The moisture content of brown rice can be obtained using several approaches (Lu et al, 2018; Qu et al, 2020), for example, the thermogravimetric method, as shown in Figure 1a. The rice specimens are stored at constant temperature and humidity chamber with the relative humidity of 65% and the air temperature of 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Freshly harvested peanuts have a moisture content of up to 50% [8], but they are highly susceptible to mold and even toxins if they are not dried in time, thereby resulting in economic losses [9][10][11]. Peanuts with less than 10% moisture can be stored for a long time [12]. With 9% moisture content, it can be stored safely for nearly 1 year at 25-27 • C and 70% RH [13].…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al (2022) explored the moisture variation law of tea during hot air drying and established the particle swarm optimization‐Elman (PSO‐Elman) model to predict the moisture content of tea in the drying process by using drying temperature, drum velocity, initial drying moisture, and drying time as input parameters. Qu et al (2020) explored the drying characteristics of peanuts during hot air drying, and established a support vector regression (SVR) model with hot air temperature, initial moisture content, air flow rate, and floor height as input parameters to predict the moisture content of peanuts in the drying process. This study conducted the experimental study in a more complex environment (segmental drying) and proposed a new model for predicting the moisture variation of PNT in the process of segmental drying.…”
Section: Introductionmentioning
confidence: 99%